2021
DOI: 10.1093/cid/ciab528
|View full text |Cite
|
Sign up to set email alerts
|

Global Respiratory Syncytial Virus–Related Infant Community Deaths

Abstract: Background Respiratory syncytial virus (RSV) is a leading cause of pediatric death, with >99% of mortality occurring in low- and lower middle-income countries. At least half of RSV-related deaths are estimated to occur in the community, but clinical characteristics of this group of children remain poorly characterized. Methods The RSV Global Online Mortality Database (RSV GOLD), a global registry of under-5 children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 10 publications
0
28
0
8
Order By: Relevance
“…Although not being a common cause of deaths in the neonatal period, RSV was in the causal chain for about 19% of RSV-attributable deaths in children aged 0–6 months. A study 25 based on global case series of RSV mortality reported a greater proportion of RSV neonatal deaths in community than in hospitals. These findings highlight the need for RSV maternal vaccine or a birth-dose of RSV monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Although not being a common cause of deaths in the neonatal period, RSV was in the causal chain for about 19% of RSV-attributable deaths in children aged 0–6 months. A study 25 based on global case series of RSV mortality reported a greater proportion of RSV neonatal deaths in community than in hospitals. These findings highlight the need for RSV maternal vaccine or a birth-dose of RSV monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viruses are the most frequent cause of disease in humans, having significant impacts on morbidity and mortality worldwide [ 21 , 22 , 23 ]. The most common respiratory viruses are endemic agents such as coronaviruses (CoVs), respiratory syncytial viruses (RSVs), and influenza (flu) viruses.…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…RSV strains A and B co-circulate having no significant correlation with disease severity [ 31 , 32 ]. RSV is estimated to cause >3 million hospitalizations and 95,000–150,000 deaths globally each year, where up to 175,000 hospitalizations in the United States are children < 5 years of age [ 21 , 33 , 34 ]. RSV is also estimated to cause > 14,000 deaths/year in adults in the United States.…”
Section: Respiratory Virusesmentioning
confidence: 99%
“…As Infecções Respiratórias Agudas (IRA) continuam sendo a principal causa de morbimortalidade em todo mundo, principalmente em crianças menores de cinco anos (1)(2) . Um dos vírus causadores de IRA é o Vírus Sincicial Respiratório (VSR); é mais prevalente em crianças; a maioria delas é infectada até 12 meses de idade e quase todas, até completarem dois anos de vida (3)(4)(5) . O VSR responde como principal agente causador da bronquiolite e pneumonia e relaciona-se, mundialmente, a surtos e infecções simultâneas em doenças respiratórias (6) .…”
Section: Introductionunclassified